European Petroleum Conference 1992
DOI: 10.2118/25073-ms
|View full text |Cite
|
Sign up to set email alerts
|

On the Transport Properties of a Rod-Type Polymer in Sand Packs

Abstract: Determination of rheological parameters of rod-type bio-polymer (Xanthan) solutions as a single (mobile) phase in sand packs is discussed. In one series residual oil is present. Apparent viscosities approximated from sand pack experiments could be described by a Carreau type of equation. Since no real in situ polymer solution viscosities and permeabilities to these solutions can be determined up to now a practical way out of this problem is the determination of mobilities to the polymer solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In reservoir cores at residual oil saturation (ROS), Vela et al (1976) found HPAM (Dow Pusher 700) retention values increased from approximately 12 lg/g in 137-md sandstone to approximately 130 lg/g in 12-md sandstone. Along with this increase in polymer retention, resistance factors and residual resistance factors increased by factors from 13 to 20.…”
Section: Literature Review Of Factors Affecting Polymer Retentionmentioning
confidence: 99%
“…In reservoir cores at residual oil saturation (ROS), Vela et al (1976) found HPAM (Dow Pusher 700) retention values increased from approximately 12 lg/g in 137-md sandstone to approximately 130 lg/g in 12-md sandstone. Along with this increase in polymer retention, resistance factors and residual resistance factors increased by factors from 13 to 20.…”
Section: Literature Review Of Factors Affecting Polymer Retentionmentioning
confidence: 99%
“…The apparent viscosity of each solution was estimated using Darcy's law and a measure of the polymer flow rate through the medium at each hydraulic gradient (Table ). This method has been described in the literature by previous researchers ( ).…”
Section: Resultsmentioning
confidence: 99%